Quantitative Criminology: An Evaluation of Sources of Crime Data (Global Journal of Human-Social Science, 2016)
Crime data is at the heart of quantitative criminology research in particular and social science research in general. In the past years, many sources of crime data have been proposed to understand, describe and explain crime and criminality, but never before have the majority of these sources been tested using a huge number of crimes and applying different multivariate methods. A large-scale analysis and comparison of various sources of crime data is crucial if current analytical methods are to be used effectively and if new and more powerful methods are to be developed. This article presents the results of a comparison of the four main sources of crime data commonly used in quantitative criminology, in order to determine the best data source that can tell the whole truth about the extent or the true level of crime occurring in a society. Based on the results of these tests, a more comprehensive approach to measure crime is proposed, which represents all categories of crime and covers the offences committed. The result of the analysis is empirically-based, objective, and replicable evidence which can be used in conjunction with existing literature on the quantitative methods in criminology.
Keywords: quantitative; multivariate; hierarchical; vector; space; matrix; SOM; Euclidean distance; Prison statistics; Court records; PCR; CSEW